The Intellectual Developments During the AlMohad Dynasty (1130-1269): Some Preliminary Remarks - Bensaid, Benaouda; Grine, Fadila (IDOSI, 2011)
Much has been written about the acclaimed Mahdi Ibn Tumart (1080–1130), the theological doctrine of AlMohads and their tireless efforts to extinct Malikism in the Maghreb. Such a development and Ibn Tumart’s claim of Mahdism caused AlMohads’ contributions to be totally or partially obscured while AlMohads shows significantly prosperous intellectual life. This research examines the background of the intellectual developments during AlMohad Dynasty, and their influence on advancing learning and scholarship. This inquiry not only helps highlight the effects of earlier dynasties on AlMohads intellectual life but also repositions the distinct theological character of AlMohads in the process of intellectual and legal development in the Maghreb.